37.3k views
23 votes
Find the coefficient of x in the expansion of ( x + 6 )(x + 7)

User Tergiver
by
5.5k points

1 Answer

11 votes

Answer: 13

========================================================

Step-by-step explanation:

You can use the FOIL rule to expand out the given expression and you should get
x^2+13x+42

Or you can follow this set of steps


(x+6)(x+7)\\\\y(x+7) \ \ \text{ ... let y = x+6}\\\\xy+7y\\\\x( y )+7( y )\\\\x( x+6 )+7( x+6 ) \ \ \text{ ... plug in y = x+6}\\\\x^2+6x+7x+42\\\\x^2+13x+42\\\\

Whichever method you use, the x coefficient is 13.

User Marek H
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.